The Randomized American Option as a Classical Solution to the Penalized Problem - Leduc, Guillaume (2015)
In this paper, we connect the randomized American option to the penalty method, showing that not only does its value u solve the canonical penalty problem, but also it is a classical solution to this Cauchy problem and, for a given maturity, Au is bounded.